References of physical growth for gaúchos and catarinenses adolescents - Maria Fátima Glaner (Universidade Federal de Santa Catarina, 2003)
The objective of this study was to establish percentiles for the variables that characterize physical growth and to compare body mass and stature with criterion-referenced standards established by Marcondes (1982) for body mass and stature and, by AAHPERD (1988) for body mass index. 1420 volunteer students from public schools comprised the sample. 699 were girls and 721 were boys aged from 10.50 to 17.49 years old. Variables were processed with the Statistical Analysis System, by decimal age for each sex. It can be concluded from the results that: 90% of the sample were shown to have normal physical growth as expressed by body mass and stature (Marcondes, 1982); 84% of girls and 79% of boys do match the criterion-referenced, indicators for body mass index (AAHPERD, 1988). RESUMO Este estudo teve por objetivo estabelecer percentis para as variáveis que caracterizam o crescimento físico e, analisar os dados obtidos em relação aos critérios de referência para massa corporal e estatura (Marcondes, 1982) e índice de massa corporal (AAHPERD, 1988). A amostra foi composta por 1420 estudantes voluntários, de escolas públicas, sendo 699 moças e 721 rapazes, com idades entre 10,50 e 17,49 anos. As variáveis foram tratadas no Statistical Analysis System, por idade decimal no mesmo sexo. Os resultados obtidos possibilitam concluir que: 90% da amostra apresentam crescimento físico normal (Marcondes, 1982),expresso pela estatura e massa corporal; 84% das moças e 79% dos rapazes apresentam índice de massa corporal satisfatório (AAHPERD, 1988).